Molecular Docking Study of Illicium verum Hook f. as Elastase and Collagenase Inhibitor in Anti-aging Mechanism - Rahman, Ave; Widiandani, Tri; Widyowati, Retno (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Skin aging, a natural physiological process intensified by external factors that augment the activity of aging-related enzymes such as elastase and collagenase, leads to the degradation of collagen solubility and the disruption of elastin fiber cross-linking. This study aimed to investigate the potential of secondary metabolites from Illicium verum fruit as inhibitors of both elastase and collagenase through an in silico molecular docking approach. The methodology involved ligand and protein preparation, validation of the docking protocol, the molecular docking simulation itself, and subsequent visualization of amino acid residue interactions. The protein targets utilized were elastase (PDB ID: 1Y93) and collagenase (PDB ID: 2D1N). The docking results identified gingerol as exhibiting the highest binding affinity for elastase (-7.99 kcal/mol), followed by carvacrol (-6.79 kcal/mol) and ferulic acid (-6.24 kcal/mol). Similarly, for collagenase, gingerol displayed the strongest interaction (-8.47 kcal/mol), followed by carvacrol (-6.30 kcal/mol) and α-pinene (-6.24 kcal/mol). Notably, gingerol and carvacrol also demonstrated favorable amino acid similarity scores and promising interactions within the active sites of both elastase and collagenase. In conclusion, this molecular docking study suggests that the secondary metabolites of I. verum fruit possess potential anti-aging activity by inhibiting elastase and collagenase enzymes.